PROCEDE: A failed programme to reduce poverty and inequalities in Mexico - Ana De Ita (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper analyses the land tenure reform that took place in Mexico in 1992 and its PROCEDE programme (Ejido Rights Certification Programme). It considers the counter-agrarian reform's objectives, the context in which it was proposed, and the different actors involved. It delves into the main points of debate, the mechanisms used to finally get the reform approved. Although this reform was not part of an explicit policy to reduce ethnic inequalities, its proponents argued that it would reduce the poverty of peasants and indigenous people. Almost 30 years after this reform was enacted, it is necessary to analyse its results. We consider how the subsequent political landscape influenced the evolution of PROCEDE, the agrarian structure changes, the collective ownership of land, and the political situation of the ejidos and communities in the new scenario.
Keywords: Q1; Q15; Q18; 330; land tenure; agrarian structure; collective ownership of land; counter-agrarian reform; poverty of peasants and indigenous people